2017
DOI: 10.1111/odi.12682
|View full text |Cite
|
Sign up to set email alerts
|

Oral mycobiome in community‐dwelling elderly and its relation to oral and general health conditions

Abstract: Candida albicans, C. glabrata, and C. dubliniensis dominated the oral mycobiome in Japanese community-dwelling elderly. Lower BMI might signify compromised health status and thus could result in susceptibility to specific candidiasis by C. glabrata and C. dubliniensis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 43 publications
(70 reference statements)
3
35
1
3
Order By: Relevance
“…In another recent study, Zakaria et al. () noted that the oral cavities of those with lower BMI (body mass index) were more frequently colonized with Candida dubliniensis and Candida glabrata while those with lower salivary flow rates were colonized by C. albicans . Nonetheless, new studies using novel, culture‐independent analyses, such as NGS technology, are needed to re‐evaluate the fungal diversity in human mouth under changing physiological and chronological conditions as historical data are likely to be biased towards the yeasts that flourished in conventional laboratory culture.…”
Section: Oral Mycobiome and Oral Physiologymentioning
confidence: 98%
See 1 more Smart Citation
“…In another recent study, Zakaria et al. () noted that the oral cavities of those with lower BMI (body mass index) were more frequently colonized with Candida dubliniensis and Candida glabrata while those with lower salivary flow rates were colonized by C. albicans . Nonetheless, new studies using novel, culture‐independent analyses, such as NGS technology, are needed to re‐evaluate the fungal diversity in human mouth under changing physiological and chronological conditions as historical data are likely to be biased towards the yeasts that flourished in conventional laboratory culture.…”
Section: Oral Mycobiome and Oral Physiologymentioning
confidence: 98%
“…In comparison with the elderly, the carriage of Candida in the oral cavities of infants at birth is lower and colonization rates rise with age reaching adult carriage rates in the first year of life (Kleinegger, Lockhart, Vargas, & Soll, 1996;Russell & Lay, 1973;Ward, Knights, & Gale, 2017). In another recent study, Zakaria et al (2017) noted that the oral cavities of those with lower BMI (body mass index) were more frequently colonized with Candida dubliniensis and Candida glabrata while those with lower salivary flow rates were colonized by C. albicans. Nonetheless, new studies using novel, culture-independent analyses, such as NGS technology, are needed to re-evaluate the fungal diversity in human mouth under changing physiological and chronological conditions as historical data are likely to be biased towards the yeasts that flourished in conventional laboratory culture.…”
Section: Or Al Mycob Iome and Or Al Phys Iologymentioning
confidence: 99%
“…The high prevalence of Candida in the oral cavity is consistent with previous culture-based studies, and subsequent molecular studies confirmed the high prevalence of Candida spp. within the oral cavity, reporting Candida albicans , Candida parapsilosis and Candida dubliniensis as the most abundant oral Candida species [ 26 , 29 , 30 ].…”
Section: The Mycobiomementioning
confidence: 99%
“…Over the last ten years, some studies have found an increase in the Non-Albicans Candida (NAC) recovery frequency in oral mucosa: from 10 % in 1996 [15] to 15.0% [16] in 2010, 15.4 % in 2011 [17], and 20.0% in 2017 [35] in the case of C. parapsilosis at the level of healthy subjects. Among the local and/or systemic factors associated with the higher distribution of NAC species in the oral cavity, we could mention the use of prosthetic devices; [64] being elderly [65], elderly with low body mass index [66]; being an oncological patient undergoing chemotherapy or radiotherapy…”
Section: Oral Mucosa As a Potential Source Of Candidemia By Candida Pmentioning
confidence: 99%